The Influence of Social Rehabilitation Programs on Behavioral Transformation of Prisoners at Class IIA Tanjungpinang Narcotics Penitentiary - Rianto, Rianto; Nengsih, Neng Suryanti; Arfa, Desmayeti; husni, Alfi; Riandy, Denis Victor (Journal of Social and Policy Issues, 2024)
This study aims to examine the influence of social rehabilitation programs on behavioral changes among inmates at the Class IIA Tanjungpinang Narcotics Penitentiary. Utilizing a quantitative associative approach, 140 inmates participating in the program were selected as samples through a simple random sampling method. Data were collected via questionnaires and analyzed using SPSS version 21. The findings reveal that the social rehabilitation program significantly impacts behavioral changes in inmates, evidenced by an r-count value of 0.563. Furthermore, the R-square value of 0.563 indicates that the program accounts for 56.3% of the observed behavioral changes, while the remaining 43.7% is attributed to other unexamined variables. Statistical testing using ANOVA yielded an F-value of 131.254, which is greater than the F-table value of 3.09, with a significance level of 0.000 (< 0.05), confirming a positive and significant relationship between the program and behavioral changes. The study concludes that the social rehabilitation program implemented at the Class IIA Tanjungpinang Narcotics Penitentiary effectively improves inmates' behavior. This highlights the program's potential as a strategic intervention in fostering positive behavioral transformations among inmates, contributing to their reintegration into society.